Anisotropic Chemical Etching of III—V Crystals Dissolution Slowness Surface and Application to GaAs - C. R. Tellier; G. Huve; T. G. Leblois (Active and Passive Electronic Components)
The analytical equation for the dissolution slowness surface of III–V crystals that belong to point group 4¯3 m is derived using a tensorial analysis of the anisotropic chemical dissolution. The role played by orientation functions in the generation of the dissolution slowness extrema is discussed. Four different databases composed of dissolution constants are proposed. The final shape of cross-sectional dissolution profiles etched in differently oriented GaAs surfaces is analyzed and compared with published experimental results. Finally etching shapes of micromachined membranes and mesa are derived showing that the anisotropy for the GaAs crystal is probably of type 2 rather than of type 1.